Artesunate-, sulfadoxine-, and pyrimethamine-induced cardiotoxicity - Divya Goel; Shafiqa Aslam; Rani Walia; Akshay Sadhotra (Wolters Kluwer Medknow Publications, 2016)
Here, we report oral artesunate, sulphadoxine and pyrimethamine (sp) induced cardio toxicity case in a female patient. Artesunate is a highly efficacious and relatively safe antimalarial drug. Common adverse reactions to artemisinin derivatives are mild i.e. nausea, vomiting, anorexia and dizziness which are seen in majority of the patients. While serious toxic effects of artesunate are less frequent i.e., neutropenia, anemia, hemolysis, elevated liver enzymes, allergic reactions and cardiac effects. Cardiac effects due to artesunate are very rare. This case recalls the artesunate potential to cause myocardial injury.